A palliative approach to spirituality in residential aged care - Kristjanson, Linda (The Haworth Press, 2006)
This paper describes how a palliative approach to care is relevant in the context of residential aged care, with specific focus on the spiritual needs of residents. Three issues are described that make attention to spirituality in residential aged care particuarly challenging; effects of cognitive changes, potential threats to dignity, and uncertainties about how to provide bereavement support to the range of people who experience loss in this care context. Reflections on how residential aged care staff might better assess the spiritual needs of residents are offered with suggestions from the literature about how to sensitively respond to these needs.